Validation and verification of predictive salivary biomarkers for oral health - Bostanci, Nagihan; Mitsakakis, Konstantinos; Afacan, Beral; Bao, Kai; Johannsen, Benita; Baumgartner, Desirée; Müller, Lara; Kotolová, Hana; Emingil, Gülnur; Karpíšek, Michal (Scientific reports, 2021)
Oral health is important not only due to the diseases emerging in the oral cavity but also due to the direct relation to systemic health. Thus, early and accurate characterization of the oral health status is of utmost importance. There are several salivary biomarkers as candidates for gingivitis and periodontitis, which are major oral health threats, affecting the gums. These need to be verified and validated for their potential use as differentiators of health, gingivitis and periodontitis status, before they are translated to chair-side for diagnostics and personalized monitoring. We aimed to measure 10 candidates using high sensitivity ELISAs in a well-controlled cohort of 127 individuals from three groups: periodontitis (60), gingivitis (31) and healthy (36). The statistical approaches included univariate statistical tests, receiver operating characteristic curves (ROC) with the corresponding Area Under the Curve (AUC) and Classification and Regression Tree (CART) analysis. The main outcomes were that the combination of multiple biomarker assays, rather than the use of single ones, can offer a predictive accuracy of > 90% for gingivitis versus health groups; and 100% for periodontitis versus health and periodontitis versus gingivitis groups. Furthermore, ratios of biomarkers MMP-8, MMP-9 and TIMP-1 were also proven to be powerful differentiating values compared to the single biomarkers.
Keywords: dospělí; Enzyme-Linked Immunosorbent Assay; Female; biologické markery; Matrix Metalloproteinase 8; Biomarkers; Oral Health; Adult; ženské pohlaví; průřezové studie; sliny; Periodontitis; matrixová metaloproteinasa 8; lidé; studie případů a kontrol; Matrix Metalloproteinase 9; kohortové studie; ROC křivka; tkáňový inhibitor metaloproteinasy 1; Humans; Cohort Studies; gingivitida; ELISA; Cross-Sectional Studies; Male; Saliva; matrixová metaloproteinasa 9; Case-Control Studies; Tissue Inhibitor of Metalloproteinase-1; Gingivitis; orální zdraví; lidé středního věku; plocha pod křivkou; mužské pohlaví; parodontitida; Middle Aged; ROC Curve; Area Under Curve